A rare case of acquired infantile Bell’s palsy - Mulinja, Lakshmi; Mohammed, Thanzir; Govindarajan, Varun; Kariyappa, Mallesh (International Journal of Contemporary Pediatrics, 2021)
Bell’s palsy, an acute onset, acquired, isolated peripheral facial palsy, usually follows a viral illness, is common disorder post infancy to adolescence. It has a favourable prognosis with spontaneous resolution, or with use of oral corticosteroids. Its presentation in early infancy is very unusual, as in our case report of 3 month old infant with an ovoid mass lesion in parotid, which disappeared after therapy with corticosteroids with no residual deficit.